21st Century Schools’ Leaders: the Lead Teachers’ Positive Influence on the Teachers and the Students A Study in a Private School in Dubai - SUBRI, NOUR ABDULLAH MAHMOUD (2018)
This research study investigates the influence of the lead teachers’ role on the teachers’ motivation and professional development, and it explores the influence of the lead teachers’ role on the teaching and learning process along with the main challenges that face the lead teachers in their role in a private school in Dubai. The aim in this study to examine the positive relationship between the effective lead teachers’ role with the improvement in the teaching and learning process, teachers’ motivation to work, and teachers’ professional development. Triangulation method was adopted in research for completeness and conformity purposes; a close-ended questionnaire (quantitative data) was sent to 104 teachers in the school, and standardized open-ended interviews were conducted with 20 lead teachers in different schools in Dubai who are currently in their role. The researcher received 37 responses only out of 104 teachers in the mentioned school. Survey Monkey Software was used in collecting and presenting the quantitative data while Nvivo Software was used in presenting the qualitative data. SPSS Software was used in analyzing the quantitative data. The analysis of the quantitative data of the study shows that there is a positive relationship between the effective lead teachers and the improvement in teaching and learning process, teacher’ motivation to work, and teachers professional development. In corresponding with the analysis of the quantitative data, the qualitative data reconsolidates and confirms the quantitative data findings, and it indicates that lead teachers face many challenges in their role as teachers and leaders in the same time that constrains their work such as time and resources shortage, work overload and teachers’ reluctant. At the end of the study, the research study’s limitations were highlighted and few recommendations were suggested in the further studies in the future in order to cover and to include other leadership aspects that could affect on the schools’ improvement in UAE.